Pengaruh Kualitas Layanan, Kecepatan Dan Kemudahan Terhadap Kepuasan Nasabah Gen Z Menggunakan M-Banking BSI KCP Ponorogo - Muhyiddin; Luhur Prasetiyo (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: Customer satisfaction is the key to assessing banks in meeting customer expectations. Satisfied customers tend to be loyal and can become positive promotional agents. Era 4.0 presents extraordinary developments in the banking industry. Generation Z, who relies on technology, wants responsive, easy-to-access, seamless banking services. Research Methods: Researchers used quantitative methods (primary data). The sample was 100 responses using a non-probability sampling technique using incidental sampling. Data was collected using a questionnaire method, the instrument used a Likert scale. Data is processed with the SPSS 23 application. Results: These findings show that the service quality variable does not affect the overall satisfaction of Gen Z BSI KCP Ponorogo Soetta customers. The speed and convenience variables affect the overall satisfaction of Gen Z BSI KCP Ponorogo Soetta customers. However, service quality, speed, and convenience simultaneously influence the satisfaction of Gen Z BSI KCP Ponorogo Soetta customers. Conclusion: This research explains the influence of service quality, speed, and convenience on customer satisfaction of Gen Z BSI KCP Ponorogo Soetta. The service quality variable does not significantly influence Gen Z customer satisfaction at BSI KCP Ponorogo Soetta (sig X1 = 0.060 > 0.05), while speed (sig partially significant. Simultaneously, these three variables influence customer satisfaction (sig=0.000), contributing 55.0% to customer satisfaction, while other variables outside the model influence the remaining 45.0%.